The Effect of Edpuzzle as Learning Media for Junior High School Students’ Writing Skill - Khuluq, Dimas Ageng Kusnul; Aminin, Zainul (English Education Department, 2024)
These days, technology mostly contributes to education, particularly for students who wish to learn English writing. Edpuzzle is an innovative educational tool designed to teach English. This app is a video-content-based learning tool that may be developed for the benefit of the students. As thus, the key objective of the current research is to aid teachers in using Edpuzzle as a means of instruction for junior high school students with the objective to determine the effect it has on their abilities to write. The present research was conducted quantitatively and utilized a pre-experimental approach. According to the research's design, the researcher has given a writing assessment to 32 students as a sample over this research. Pretests and posttests, which are written assessments, were the research instruments utilized in this research. The research came across that Edpuzzle were having significant effects on the abilities to write of 8th junior high school students. The researcher admits as the current study may not have been finest; there were several barriers or weaknesses experienced throughout the procedure. As an outcome, it is uncertain that what was discovered of the present research can be generalized to wider populations or overseas.